Role of mucinohistochemical analysis in verification of malignant potential of colorectal adenoma - Radovanović-Dinić Biljana; Katić Vuka; Nagorni Aleksandar; Stamenković Ivanka (Vojnosanitetski Pregled)
Background/Aim. It is a general opinion that the biggest number of colorectal carcinoma (CRC) develops with the malignant alteration of colorectal adenomas (adenoma carcinoma sequence). Malignant potential of adenoma is in the function of its size, histological structure and the grade of dysplasia. An adequate analysis of colorectal adenomas helps their definition and timely removal, which significantly decreases carcinoma incidence. Mucin analysis can provide results which support the adenoma carcinoma sequence theory. The aim of the study was to present histochemical characteristics of adenomas and emphasize the significance of these analyses for the precise adenoma definition. Methods. This prospective study included analysis of 117 colorectal adenomas obtained by transcolonoscopic biopsy or polipectomy in 82 patients. The biopsy samples and the removed polyps were coloured by hematoxilin-eozin (HE) staining and histochemical stainings by Periodic Acid Schiff (AB-PAS) and High Iron Diamine/Alcian blue (HIDAB; pH=2.5) to prove mucins. Results. Sulphomucins are more often found in adenomas of the left colon than of the right one (p < 0.001). Sialomucins are more reactive in adenomas of the right colon (p < 0.001). Sulphomucins are more reactive in adenomas of < 10 mm diameter (p < 0.05). The reactivity of all mucins is in negative correlation with the degree of dysplasia (p < 0.001). There is a significant difference in the reactivity of sialomucins in adenomas of the same histological type but different degree of dysplasia (χ2 = 25,743, df = 6, p < 0.001). Conclusion. The difference in the presence of mucins between adenomas of the left and right colons supports the theory of adenoma carcinoma sequence, since adenomas of the right colon are more protected by sialomucins and therefore less malignantly altered, which is consistent with CRC topography. Histochemical analysis of colorectum is significant for more accurate gradation of dysplasia and confirmation of malignant alteration. The negative correlation between the degree of dysplasia and the production of mucin indicates the significance of the degree of dysplasia in malignant potential of colorectal adenomas.